2002
DOI: 10.1002/mus.10298
|View full text |Cite
|
Sign up to set email alerts
|

Severe prognosis in a large family with hypokalemic periodic paralysis

Abstract: Hypokalemic periodic paralysis (HypoPP) is a channel disorder caused primarily by mutations in the human skeletal muscle alpha1 subunit (CACNA1S) of the dihydropyridine-sensitive calcium channel. Molecular, clinical, and biochemical studies were aimed at establishing genotype/phenotype correlations in a large Italian family affected by a severe form of HypoPP. Whereas patients with HypoPP usually show a normal life span, in this family three male patients died young, one of them from anesthetic complications r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…These MHS mutations are distinct from those in Ca V 1.1 associated with HypoPP, and none of these patients had episodes of periodic paralysis. Conversely, there is a lack of agreement about whether HypoPP carries a slightly increased risk of MHS (24, 135, 155). …”
Section: Calcium Channelopathies Of Skeletal Musclementioning
confidence: 99%
“…These MHS mutations are distinct from those in Ca V 1.1 associated with HypoPP, and none of these patients had episodes of periodic paralysis. Conversely, there is a lack of agreement about whether HypoPP carries a slightly increased risk of MHS (24, 135, 155). …”
Section: Calcium Channelopathies Of Skeletal Musclementioning
confidence: 99%
“…The long-term prognosis is generally good, and crises may decrease in midlife. However, severely affected families were reported, and involvement of respiratory muscles may lead to death [7]. The discovery of single missense CACNA1S mutations in humans with HPP-1 which still allow expression of a full-length Ca v 1.1 α1 subunit protein suggested that changes in channel gating or channel expression on the cell surface may account for altered skeletal muscle function.…”
Section: Cav11 Channelopathies (Cacna1s Gene)mentioning
confidence: 99%
“…CACNA1S is composed of four homologous domains (DI-DIV), each of them consisting of six transmembrane segments (S1-S6) [9]. Three specific mutations have been identified in the CACNA1S gene in families with HypoPP: Arg528His in DIIS4, and Arg1,239His and Arg123Gly in DIVS4 [3,[10][11][12][13][14][15][16][17][18][19][20]. These mutations are all missense mutations where an arginine residue is replaced by either a histidine or sometimes a glycine residue.…”
Section: Introductionmentioning
confidence: 99%